2010
DOI: 10.3762/bjoc.6.13
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic incorporation of Nile Blue into DNA using 2′-deoxyriboside substitutes: Representative comparison of (R)- and (S)-aminopropanediol as an acyclic linker

Abstract: SummaryThe Nile Blue chromophore was incorporated into oligonucleotides using “click” chemistry for the postsynthetic modification of oligonucleotides. These were synthesized using DNA building block 3 bearing an alkyne group and reacted with the azide 4. (R)-3-amino-1,2-propanediol was applied as the linker between the phosphodiester bridges. Two sets of DNA duplexes were prepared. One set carried the chromophore in an A-T environment, the second set in a G-C environment. Both were characterized by optical sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…(ii) How important is the S -configuration of the linker? Fluorescence quenching studies with nile blue revealed that the interactions between the fluorophore and the adjacent base pairs seem to be similar with the S - and R -configurated linker …”
Section: Concept Of Dna Base Substitution: Lessons From Ethidium and ...mentioning
confidence: 95%
“…(ii) How important is the S -configuration of the linker? Fluorescence quenching studies with nile blue revealed that the interactions between the fluorophore and the adjacent base pairs seem to be similar with the S - and R -configurated linker …”
Section: Concept Of Dna Base Substitution: Lessons From Ethidium and ...mentioning
confidence: 95%
“…In former work, we already showed that 2′-deoxyribofuranoside can be replaced by a clickable acyclic linker 31 using both enantiomers. 32 Glycol is the smallest possible connection between the phosphodiester bridges as evidenced by the glycol nucleic acids (GNAs). 33 To place the dyes into the DNA base stack, we designed the clickable components 1 with the (S)configuration and 2 with the (R)-configuration at the central carbon atom.…”
Section: ■ Introductionmentioning
confidence: 99%
“…As alternatives to natural‐like nucleosides, acyclic nucleoside substitutes—containing, for example, 3‐aminopropane‐1,2‐diol as an acyclic linker between the phosphodiester units and the propargyl group for the click‐type reactivity attached through a carbamate function—have also been applied 19. The S configuration of the linker in 4 was chosen in analogy to the chirality of position 3′ in the 2′‐deoxyribofuranoside moiety of a natural nucleoside; however, the R configuration (building block 5 ) could also be applied 22…”
Section: Copper‐catalyzed Azide–alkyne Cycloaddition (Cuaac) and Tmentioning
confidence: 99%